Puzzle Ocean - Susannah Leigh (LondonUnited Kingdom Usborne Publishing Ltd, 1996)
This is a story linked with picture puzzles. There is a thief in Puzzle Ocean! When Rosie receives a message in a bottle, asking her to help track down the king's missing crown, she begins at once. She has an underwater adventure, dodging scary sharks and meeting friendly dolphins.
Keywords: oceans and Puzzles -- oceans and Puzzles